2018
DOI: 10.1111/pace.13526
|View full text |Cite
|
Sign up to set email alerts
|

Improving the utilization of implantable cardioverter defibrillators for sudden cardiac arrest prevention (Improve SCA) in developing countries: Clinical characteristics and reasons for implantation refusal

Abstract: Background: Despite available evidence that implantable cardioverter defibrillators (ICDs) reduce all-cause mortality among patients at risk for sudden cardiac death, utilization of ICDs is low especially in developing countries.Objective: To summarize reasons for ICD or cardiac resynchronization therapy defibrillator implant refusal by patients at risk for sudden cardiac arrest (Improve SCA) in developing countries.Methods: Primary prevention (PP) and secondary prevention (SP) patients from countries where IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Avoidance of fluoroscopy may contribute to reducing the economical barrier that precludes extensive device implantation in developing countries. In a multinational study seeking to determine reasons for cardiac implant refusal, inability to pay for the procedure was cited as the most common reason for implant refusal 15 …”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of fluoroscopy may contribute to reducing the economical barrier that precludes extensive device implantation in developing countries. In a multinational study seeking to determine reasons for cardiac implant refusal, inability to pay for the procedure was cited as the most common reason for implant refusal 15 …”
Section: Discussionmentioning
confidence: 99%
“…34 The Improve SCA study found the main reasons to be financial, reimbursement issues, and not believing in the benefits of the therapy. 35 A recent study in Turkey found that only one-third of eligible chronic HF patients receive a…”
Section: Adherence To Icd Therapy Effect On Mortalitymentioning
confidence: 99%
“…The reasons for refusal were documented for patients who chose not to undergo implantation, and patients could select multiple reasons. 17 Patient follow-ups were completed in person or by telephone every 6 months postimplantation or postrefusal until study closure. Patients with SP indications who did not receive an implant were exited, as they would not contribute to the objectives of the study.…”
Section: Follow-up and Data Collectionmentioning
confidence: 99%